2020
DOI: 10.4095/322191
|View full text |Cite
|
Sign up to set email alerts
|

Indicator-mineral signatures of the Casino porphyry Cu-Au-Mo deposit, Yukon

Abstract: This open file reports the results of an indicator mineral case study carried out around the Casino porphyry Cu-Mo-Au deposit in the unglaciated terrain of the west central Yukon. The research was part of the Geological Survey of Canada's (GSC) Targeted Geoscience Initiative 5 (TGI-5) Program. The purpose of the study was to test the use of indicator minerals as a porphyry Cu exploration tool in unglaciated terrain. At 22 sites around the deposit, a bulk stream sediment sample was collected to document the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Table A1), similar to that reported for bedrock samples. Several 25-to 100-µm gold grains were recovered from mineralized, tourmaline-bearing Patton porphyry bedrock samples examined in this study (McClenaghan et al, 2020); this is similar to the gold grain size range (50-70 µm) reported by Huss et al (2013) for the hypogene zone. Chapman et al ( 2014) reported a broader size range (5-1,000 µm) in Casino bedrock samples.…”
Section: Goldsupporting
confidence: 88%
See 3 more Smart Citations
“…Table A1), similar to that reported for bedrock samples. Several 25-to 100-µm gold grains were recovered from mineralized, tourmaline-bearing Patton porphyry bedrock samples examined in this study (McClenaghan et al, 2020); this is similar to the gold grain size range (50-70 µm) reported by Huss et al (2013) for the hypogene zone. Chapman et al ( 2014) reported a broader size range (5-1,000 µm) in Casino bedrock samples.…”
Section: Goldsupporting
confidence: 88%
“…Grain counts for selected indicator minerals are reported both in Table 3 and below as values normalized to 10 kg of <2-mm material to allow comparison between heavy mineral samples of different masses. Individual mineral distribution maps are included in McClenaghan et al (2020) and are summarized below. Unless otherwise stated, the results are for the 0.25-to 0.5-mm >3.2-SG fraction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations